Chemical and Environmental Behaviour of Materials, The Nernst Equation and Pourbaix Diagrams
En este conjunto de animaciones se muestran diagramas de Porbaix interactivos. Contiene los siguientes elementos:Construction of a Pourbaix diagram Pourbaix diagrams built up Construction of a 3D Pourbaix diagram